Single-phase AC-AC Z-source converter based on asymmetrical gamma structure with continuous input current and safe commutation strategy - Mousavi, Seyyed Mohammad Javad; Babaei, Ebrahim; Alizadeh, Darioush; Komurcugil, Hasan (Wiley, 2021)
This paper examines a new topology of the AC-AC Z-source converter based on asymmetric Gama structure is proposed. The proposed converter has all the common features such as common ground between input and output, realizing the continuous input current and the ability of boost in-phase and buck out of-phase. In order to generate a high voltage gain in the proposed converter, a coupled inductor with Gama structure is used. In this structure, as the turn ratio approaches to one, it gives a higher voltage gain. In order to damping the voltage and current overshoots on the proposed converter switches, a safe commutation strategy is used. Due to the specific topology of the proposed converter, the output filter has been eliminated, so the size and cost of the proposed converter are reduced. Circuit analysis and performance principles are presented in detail and a laboratory prototype implemented to confirm the practicality of the proposed converter.